Analyzing Hindu Women’s Right to Property in Bangladesh: Absolute Interest versus Limited Interest - Begum, Ferdousi (Kathmandu School of Law Review, 2018)
Hindu women living in Bangladesh are deprived of inheritance in comparison to their male counterparts. They exercise a limited interest in the property while their male counterparts have an absolute interest in the property except in case of Stridhan. This feature gives a scenario of male dominating society in Bangladesh. If alienation is possible in case of Stridhan property, it ought to be applicable in case of getting properties through the way of inheritance as well; but it is not clear at all. There is no reason behind having such kind of discrimination. Therefore, this paper argues that as a Hindu woman can handle her property like a man in case of Stridhan property, she should, absolutely instead of enjoying it limitedly, enjoy all of her properties including the properties which she gets by way of inheritance as well.